Reconceptualising the teaching of heritage in schools - Moreeng, Boitumelo B (South African Journal of Higher Education, 2016)
The broader education system in South Africa, and specifically history teaching, has undergone changes that aimed, on the one hand, to cleanse the subject content of discriminatory and incriminating practices and, on the other, to affirm previously neglected histories. By so doing, the principles of democratic citizenry such as critical thinking, clear reasoning and respect for multiple perspectives were envisioned to be enhanced. This paper, using a postcolonial discourse, reports on a study conducted in the Free State Province. It seeks to add to the debate on enhancing democracy through education and to augment the creation of sustainable learning environments by means of accommodating previously neglected forms of historical knowledge and heritage conceptualisation. Qualitative focus-group interviews were used to investigate the ways in which teachers conceptualise and teach heritage during their history lessons. Findings revealed that the participants’ initial training and socialisation plays an important part in conceptualising and teaching heritage from a predominantly colonial and imperialistic perspective. This approach continues to look down upon African knowledge systems and ways in which Africans make meaning of their past. Critical learning in such environments might be compromised, as experiences and interpretations from one perspective only are promoted. It is recommended that history educators be exposed to other ways of interpreting the past, for example postcolonial discourse, as this will assist in challenging the continuing legacy of imperialism, colonialism and apartheid instilled in history educators’ and learners’ approach towards the concept of heritage. The findings of the study have a direct impact on the initial and in-service training of history teachers in that a more open way is needed of looking at the past and the exposure to multiple perspectives in the teaching of history. KEYWORDS History Teaching, Heritage, Postcolonial Discourse